Implementasi Model Manajemen Berbasis Sekolah pada MTs Swasta Al-Mushlihin Kota Binjai - Endah Retno Suci; Aris Widodo (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
The research seeks to understand the implementation of school-based management model in Mts Swasta Al-Mushlihin Binjai City. This type of research is qualitative with an inductive paradigm. Data is obtained through the results of interviews conducted with informants consisting of the Principal; Deputy Principals, Senior Teachers and related Stakeholders. The data is then processed using data triangulation techniques. The data is strengthened through the results of documentation and participant observation. The study's findings the effectiveness of managers in defining the vision, connecting with other professionals to learn about the SBM implementation process. The critical system covers aspects of social-interaction administration, technical skills, student motivation, availability of time to other technical problems. Elements of factors as well as fundamentals are the transformational leadership style and the concept of school-based management. In addition, School Based Management strategies for sustainable organizations are implemented concurrently through the stabilization of the system, work patterns, madrasa community be able to determine career goals, develop and implement plans to get the education and experience needed, and develop as an innovative professional.